Implementasi Carbon Emission Disclosure di Indonesia - Pratiwi, Desy Nur (Jurnal Ilmiah Akuntansi dan Bisnis, 2018)
Climate change is one of the global phenomena that has become the biggest environmental problem in recent years that comes from corporate carbon emissions. This study aims to get empirical evidence of factors affecting carbon emission disclosure after president regulation number 61 year 2011. We investigate four factors (regulators, institutional ownership, size and profitability) that affect disclosure of company carbon emissions. This study uses secondary data in the form of manufacturing and mining companies listed on the Indonesia Stock Exchange for the period 2012 to 2016. Hypothesis test using multiple linear regression. The sample used in this research are 30 companies. The results show that the factors affecting carbon emissions disclosure are regulators and institutional ownership, while size and profitability have no effect on carbon emissions disclosure. Keywords : Climate change, greenhouse effect, carbon emission disclosure